Content of Policy and Context of Implementation in Tourism Sector: Case Bintan Regency to Handling Covid-19 - Mahadiansar Mahadiansar; Andy Fefta Wijaya; Alfi Haris Wanto; Firda Hidayati (Jurnal Studi Pemerintahan, 2022)
This paper discusses efforts to strengthen policy implementation in handling COVID-19 in the tourism sector in Indonesia as a form of strengthening every tourism policy. This study uses the grindle concept to identify Policy Content and Implementation Context in Handling COVID-19 in the Tourism Sector of Bintan Regency. The method used is a qualitative approach including data collection techniques, observation, interviews, and documentation so that the data obtained are tested using NVivo 12 Pro, then analyzed with a triangulation approach. The results of the study indicate that the emphasis on handling COVID-19 in the tourism sector in the Regency needs to be strengthened by existing stakeholders, meaning that on the Policy Content side it consists of the interests affected, types of benefits, degree of change, location of decision making, program implementation and resources used. still focused on central regulations and rules so that local government authorities cannot initiate policy strategies for handling COVID-19 in the tourism sector in Bintan Regency. showed a good contribution in handling COVID-19 in the tourism sector in Bintan Regency.